SCREENING OF COMMERCIAL ENRICHMENT MEDIUM FOR SELECTIVE GROWTH OF E. COLI - Lawaniya, R (Indian Journal of Dairy Science, 2014)
Different selective enrichment media like Violet Red Bile agar (VRBA), Eosin Methylene Blue (EMB), Tergitol-7 (T-7), Difco MI broth and MacConkey Broth were evaluated for recovery of different strains of E. coli (25922, 11229 and 14948) with the other organisms of the enterobacteriaceae family when spiked in broth as well as in milk. The efficacy of T-7 medium was determined as a better enrichment medium for growth of pathogenic/non-pathogenic E. coli over medium like Violet Red Bile Broth (VRBB), Eosin Methylene Blue (EMB) and MacConkey Broth as compared with the growth of other organisms like S. abony NCTC 6017, S. flexneri ATCC 12022, Y. enterocolitica ATCC 23715 and S. marcescens 13880. E. coli was used as indicator organism and other organisms were treated as background microflora (contaminants) and growth pattern study were conducted by enumerating cell count after every 6.0 h of interval on their respective selective media. Growth pattern study reveals that T-7 broth could inhibit the background microflora to a more extent and simultaneously showed good recovery of target organism i.e. E. coli. The selective agents already present in the T-7 broth could be optimized and some new selective agents should be tried for better recovery regarding pathogenic/non-pathogenic E. coli and more inhibition towards background microflora.Â